Interval Type-2 fuzzy exponentially weighted moving average control chart - Akeem Ajibola Adepoju; Sauta S. Abdulkadir; Danjuma Jibasen; Haruna Chiroma (Statistics in Transition new series (SiTns), 2022)
Some industrial data often come with uncertainty, which in some cases depends on the decision of those responsible for taking the measurement in the production process. While the fuzzy approach helps to tackle the ambiguity that arises in the measurement, an interval type-2 fuzzy set deals with such uncertainty better due to its flexibility over the control limits of its control chart. This paper aims to develop an Interval Type-2 fuzzy Exponentially Weighted Moving Average Control Chart (IT2FEWMA) under the fuzzy type-2 condition. This development will facilitate monitoring small and moderate shifts in the production process in conditions of uncertainty.
Keywords: 519; Exponentially weighted moving average control chart; Fuzzy control chart; Fuzzy sets; Interval Type-2 fuzzy sets; Interval Type-2 fuzzy Exponentially Weighted Moving Average Control Chart; Statistical process control